Comparison of inhibitory effects between acetaminophen-glutathione conjugate and reduced glutathione in human glutathione reductase - Nýdlová, Erika; Vrbová, Martina; Cesla, Petr; Jankovičová, Barbora; Ventura, Karel; Roušar, Tomáš (Journal of applied toxicology, 2014)
Acetaminophen overdose is the most frequent cause of acute liver injury. The main mechanism of acetaminophen toxicity has been attributed to oxidation of acetaminophen. The oxidation product is very reactive and reacts with glutathione generating acetaminophen-glutathione conjugate (APAP-SG). Although this conjugate has been recognized to be generally nontoxic, we have found recently that APAP-SG could produce a toxic effect. Therefore, the aim of our study was to estimate the toxicity of purified APAP-SG by characterizing the inhibitory effect in human glutathione reductase (GR) and comparing that to the inhibitory effect of the natural inhibitor reduced glutathione. We used two types of human GR: recombinant and freshly purified from red blood cells. Our results show that GR was significantly inhibited in the presence of both APAP-SG and reduced glutathione. For example, the enzyme activity of recombinant and purified GR was reduced in the presence of 4 mm APAP-SG (with 0.5 mm glutathione disulfide) by 28% and 22%, respectively. The type of enzyme inhibition was observed to be competitive in the cases of both APAP-SG and glutathione. As glutathione inhibits GR activity in cells under physiological conditions, the rate of enzyme inhibition ought to be weaker in the case of glutathione depletion that is typical of acetaminophen overdose. Notably, however, enzyme activity likely remains inhibited due to the presence of APAP-SG, which might enhance the pro-oxidative status in the cell. We conclude that our finding could reflect some other pathological mechanism that may contribute to the toxicity of acetaminophen.
Keywords: Acetaminophen; glutathione; acetaminophen toxicity; Humans; glutathiondisulfid; Erythrocytes; paracetamol; Dose-Response Relationship, Drug; lidé; Recombinant Proteins; Glutathione; rekombinantní proteiny; glutathione reductase; erytrocyty; glutathion; vztah mezi dávkou a účinkem léčiva; Glutathione Reductase; glutathionreduktasa; Glutathione Disulfide